Spatial data fusion in Spatial Data Infrastructures using Linked Data. Issue 4 (2nd April 2016) - Wiemann, Stefan; Bernard, Lars
ABSTRACT: The synthesis of spatial data from the various sources available on the Web is a major challenge for current applications based on Web-based information retrieval and spatial decision-making. This article addresses spatial data fusion, with particular emphasis on its application in Spatial Data Infrastructures (SDIs). Possibilities for the integration of SDI and Semantic Web developments in the context of spatial data fusion are reviewed with a focus on the harmonized description and usage of feature relations. Specifically, potential applications of Linked Data principles are discussed in detail. On this basis, a classification and a decomposition of fusion processes in a service-oriented environment are proposed. A prototype implementation demonstrates the feasibility and usability of the approach using Open Geospatial Consortium (OGC) and Semantic Web standards.